2012
DOI: 10.1002/pat.3046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of modified poly (styrene‐alt‐maleic anhydride) networks as a nano chelating resin for uptake of heavy metal ions

Abstract: A chelating resin based on modified poly (styrene‐alt‐maleic anhydride) with 3‐aminobenzoic acid was synthesized. This modified resin was further reacted by 1,2‐diaminoethane or 1,3‐diaminopropane in the presence of ultrasonic irradiation to prepare tridimensional chelating resin for the removal of heavy metal ions from aqueous solutions. The adsorption behavior of Fe(II), Cu(II), Zn(II) and Pb(II) ions was investigated by synthesized chelating resins in various pH. Among the synthesized resins, CSMA‐AB1 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…the coordination site, we have tried a lot to generate a crystal for single crystal X ray analysis but we did not succeed. Hasanzadeh et al [35] have reported this type of acid amide metal complex. So from the obtained data and reference article, interpretations become straightforward.…”
Section: Materials and Measurementsmentioning
confidence: 87%
“…the coordination site, we have tried a lot to generate a crystal for single crystal X ray analysis but we did not succeed. Hasanzadeh et al [35] have reported this type of acid amide metal complex. So from the obtained data and reference article, interpretations become straightforward.…”
Section: Materials and Measurementsmentioning
confidence: 87%
“…In order to facilitate the correct structural assessment, that is, the coordination site, we have tried a lot to generate a crystal for single crystal X-ray analysis but we did not succeed. Hasanzadeh et al [23] have reported this type of acid amide metal complex. So from the obtained data and reference article, interpretations become straightforward.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the modified PSMA copolymer was successfully prepared by chemical graft reaction of 4ABSA on PSMA as described in our previous work [25]. Briefly, 3 g (0.015 mol) PSMA copolymer and 1.03 g (0.008 mol) 4ABSA in molar ratio of 1:0.5 were poured into a flask.…”
Section: Synthesis Of Psma-g-4absamentioning
confidence: 99%
“…Our interest for the use of this copolymer is due to the fact that PSMA is an inexpensive commercially available copolymer having reactive groups in the main structure for further functionalization [25].…”
Section: Introductionmentioning
confidence: 99%